POTABLE CENOMANIAN-CALLOVIAN GROUNDWATER COMPLEX CHEMICAL COMPOSITION CHANGES DYNAMICS IN KYIV AS A RESULT OF LONG-TERM EXPLOITATION - Koshliakova, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Purpose. Potable ground water chemical composition and quality class changes tendencies of Cenomanian-Callovian groundwater complex in Kyiv as a result of long-term exploitation were revealed. For this purpose mathematical-statistical methods and GIStechnologies were used. Methodology. In the research systemic, mathematical-statistical, geoinformational approaches, typification method and descriptive procedure were used. For mathematical and statistical processing Microsoft Excel, Statistica, Attestat software packages were chosen; for cartographic schemes construction and for spatial analysis and modelling in GIS Corel Draw, MapInfo Professional and ArcView programs were used. Findings. Kyiv potable ground water chemical composition and quality class changes investigation methodology on the basis of combined mathematical-statistical methods and geoinformatics technologies were developed. Non-parametric statistics method (MannWitney criterion), used for hydrogeochemistry data analysis, description and substantiation are given. Kyiv territory typification, based on geomorphology characteristic, was done; the most vulnerable to contamination city zones were defined. Originality. For the first time general tendency of Cenomanian-Callovian groundwater complex deterioration was revealed in Kyiv; it was determined that city potable groundwater chemical composition basic components changes of observable groundwater complex have irregular space character and depend on exploitation intension and geo-hydrogeological and geomorphological territory district structure. Also for the first time Kyiv territory typification, based on Cenomanian-Callovian potable ground water chemical composition basic components and quality class changes, was implemented; deterioration tendencies were determined. Practical value. Practical application of determined Cenomanian-Callovian complex potable ground water chemical composition and quality class changes tendencies in Kyiv will allow to prevent further ground water deterioration with the help of exploitation system optimization. Obtained results have the potential to become the basis for the potable ground water chemical composition monitoring system development in Kyiv; methodological approaches and techniques can be used for urbanized territories ground water study.